It may cost an arm and a leg: workers value and occupational fatality rates in the U.S. - Leah S. Klos; Frank B. Giordano; Stacy A. Stoffregen; Miki C. Azuma; Jin Lee (BMC, 2021)
Abstract Background The present study aims to observe how societal indicators of workers' values at the state-level are related to health and safety outcomes, particularly major injuries and fatalities in the U.S. Underscoring workforce flexibility and workability over workforce stability and safety might be indicative of the worth of workers which can be associated with occupational safety and health concerns. Methods Linear regression analysis with a log-transformed dependent variable was adopted to examine how the state-level indicators of worker value in terms of 1) minimum wage, using data from 2015; 2) average of workers' compensations for the loss of an arm, hand, leg, or foot in 2015 were concurrently and prospectively associated with occupational fatality rates averaged across 2015, 2016 and 2017. Socioeconomic contextual variables such as education level, GDP per capita, and population at the state-level were controlled for. Results The present study showed that state-level quantitative indicators of how workers are valued at work, namely minimum wage and workers' compensation benefits, were significantly and negatively associated with fatality rates in the following year. Conclusions The present study illustrates the gap in how workers are valued across the U.S. The study speaks to the importance of contextual factors regarding worker value, as they can affect outcomes of health and safety culminating at a state-level.